Obesity, Fat Mass and Immune System: Role for Leptin - Francisco, Vera; Pino, Jesús; Campos-Cabaleiro, Victor; Ruiz-Fernández, Clara; Mera, Antonio; Gonzalez-Gay, Miguel A.; Gómez, Rodolfo; Gualillo, Oreste (Frontiers in Physiology, 2018)
Obesity is an epidemic disease characterized by chronic low-grade inflammation associated with a dysfunctional fat mass. Adipose tissue is now considered an extremely active endocrine organ that secretes cytokine-like hormones, called adipokines, either pro- or anti-inflammatory factors bridging metabolism to the immune system. Leptin is historically one of most relevant adipokines, with important physiological roles in the central control of energy metabolism and in the regulation of metabolism-immune system interplay, being a cornerstone of the emerging field of immunometabolism. Indeed, leptin receptor is expressed throughout the immune system and leptin has been shown to regulate both innate and adaptive immune responses. This review discusses the latest data regarding the role of leptin as a mediator of immune system and metabolism, with particular emphasis on its effects on obesity-associated metabolic disorders and autoimmune and/or inflammatory rheumatic diseases.